Pratiche di conoscenza in carcere: uno studio sui Poli Universitari Penitenziari - Pastore, Gerardo (Il Trimestrale - The @Lab's quarterly, 2017)
This paper focuses on university education in prison. Using quantitative and qualitative methods, it examines the Italian experience of Prison University Campuses. Focusing attention on university education in prison takes the form of a particularly useful analytical and critical exercise because it permits questioning the distance between prison and society, stereotypes of the prisoner and stereotypes of prison, for example. Furthermore, it allows capturing the transformative effects of “knowledge practices” on the individual and on the system, beyond any rhetoric of treatment.